2018
DOI: 10.1016/j.ijid.2018.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Seasonality of respiratory viruses causing hospitalizations for acute respiratory infections in children in Nha Trang, Vietnam

Abstract: Our results are important for understanding the temporal risk associated with circulating pathogens in Southern Central Vietnam. Specifically, our results can inform timing of routing seasonal influenza vaccination and for when observed respiratory illness is likely viral, leading to judicious use of antibiotics in the region.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
42
2
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(52 citation statements)
references
References 53 publications
6
42
2
2
Order By: Relevance
“…Kurskaya and Machablishvili [3,6] reported that the positive rate of in uenza increased with age, which is consistent with us. Kurskaya and Dong [3,9] also reported that the highest detection rate of in uenza was in winter, Althouse [17] reported that the peak of in uenza appeared in the middle of spring (April to June). Our results show that FLUA is the dominant factor in in uenza, while Luniewska [18] reported that FLUA and FLUB were both dominant in the epidemic season.…”
Section: Discussionmentioning
confidence: 95%
“…Kurskaya and Machablishvili [3,6] reported that the positive rate of in uenza increased with age, which is consistent with us. Kurskaya and Dong [3,9] also reported that the highest detection rate of in uenza was in winter, Althouse [17] reported that the peak of in uenza appeared in the middle of spring (April to June). Our results show that FLUA is the dominant factor in in uenza, while Luniewska [18] reported that FLUA and FLUB were both dominant in the epidemic season.…”
Section: Discussionmentioning
confidence: 95%
“…We found that the climate variable beside temperature, with the strongest correlation to RR and RoS was dew point, whereas precipitation, humidity and wind-speed did not appear to be significantly related to RR and RoS (Figure 4 and 5). Dew point temperature was previously shown to strongly associate with respiratory viruses spread rate and was recently found to explain approximately one third of the variation in transmission of enteroviruses across USA 22,23 . The dew point depends on both temperature and humidity and it is defined as the temperature to which air must be cooled at constant pressure for saturation to occur.…”
Section: Discussionmentioning
confidence: 98%
“…These findings might indicate that the timing of the catechin intake is also important for the virucidal activity in humans. Many virus infections, including influenza and the common cold, more commonly cause infection in the winter, in low-temperature seasons [32,33]. The circadian timings of infections, however, are unknown, and our understanding of the timing of infection during the day is limited [34,35].…”
Section: Discussionmentioning
confidence: 99%